The Effectiveness of Murf AI in Canva on Students' English Listening Comprehension - Paquitta Anggreani Iswanto (Indonesian Journal Publisher, 2026)
Listening comprehension is one of the essential skills in English learning, yet many junior high school students still face difficulties in understanding spoken texts. This study aims to examine the effectiveness of using Murf AI in Canva to improve students’ listening comprehension skills. A quasi-experimental design was employed involving two groups: Class 8B as the experimental group and Class 8A as the control group. The experimental group was taught using Murf AI in Canva, while the control group received conventional instruction. Data were collected through pre-tests and post-tests and analyzed using the Mann–Whitney U test and effect size calculation. The results revealed a statistically significant difference between the two groups, with the experimental group achieving higher mean scores than the control group. However, the effect size was found to be small, indicating a limited magnitude of improvement. In conclusion, the use of Murf AI in Canva has a significant effect on students’ listening comprehension skills. Although the impact is relatively small, this tool can be considered an alternative strategy to support listening instruction in